Réponses

2013-05-01T17:24:48+02:00

1)  A = 9 * 3/2 - 10

   = 27/2 -10 mettre au meme dénominateur

   =  27/2-20/2 

   =  7/2

 

     B = (3/2)² - (1/3) * (-5 /2)

formule 

a/b * c/d  = a*d  /  b*c

(3/2)(3/2)  - (1/3) (-5/2)

3*2 /2*3    -  1*2  / 3*-5

6/6             -   2/ -15

mettre au meme dénominateur

6*15/6*15  -  2*6 / -15*6

90/90         -      12/ 90

78 /90 = 26/30   =  13/15

 

2) C = (2x-5)² - (2x-5)(3x -7)

a)

C = (2x-5)² - (2x-5)(3x -7)

    =  (2x-5)(2x-5) - (2x-5)(3x-7)

    = 2x*2x - 5*2x -5*2x + 5*5   - 2x*3x -2x*7    -   5*3x +5*7

    =     4x² -   10x -  10x  + 25   -   6x²    -  14x   -    15x   +  35

    =   4x² -6x²  -  10x -10x   -14x -15x  +25  +35

    =      10x²    -49 x   +60

 

b) on reprend la 2ème ligne le début du développement

     

C  = (2x-5)(2x-5) - (2x-5)(3x-7) 

     =  (2x-5) [2x-5 - 3x-7]

     =  (2x-5) (2x-3x -5+7)

     =  (2x-5)( -x +2)